La formación superior de Enfermería en Brasil: una visión histórica - Leonello, Valéria Marli (2011)
This article describes the process of the expansion of higher education in Brazilian nursing, highlighting the diversity and heterogeneity of the system. It is observed that teaching in this area developed in a very fast and disorganized fashion, as of the nineties. This growth resulted in great diversity and variety of educational institutions, which are aspects that also affect the profile of the faculty, particularly their title and working arrangements, which vary according to their institutional placement. It is argued that these aspects will, eventually, affect the faculty, and, thus, in the early nursing training, in the qualification of nurses, and, therefore, in the nursing care offered to users of different health services. In conclusion, it is necessary to identify the professional profile and the particular working processes, contextualized in the current setting of the public policies for higher education in Brazil.